Institutional Relations of the Ombudsman with the House of Representatives of the Republic of Indonesia: Instrumental Design and Governance - Redi, Ahmad; Bakry, Mohammad Ryan (APPTHI, 2020)
The Ombudsman of the Republic of Indonesia (Ombudsman Republik Indonesia/ORI) is an institution that has the authority to supervise public services by state administrators, the government, including every person and legal entity assigned the task of administering certain public services whose financing is from the State Budget (Anggaran Pendapatan dan Belanja Negara/APBN) and Regional Budget (Anggaran Pendapatan dan Belanja Daerah/APBD). However, in carrying out its duties, ORI has the potential to face independence and accountability challenges from the House of Representatives (Dewan Perwakilan Rakyat/DPR), which carries out the functions of legislation, budgeting, and supervision. These three functions of the DPR are related to the existence of ORI in carrying out its duties. This paper discusses the position, function, and institutional relationship between ORI and the DPR. The method used is a qualitative approach, with a library study data collection technique and data analysis techniques through qualitative analytical descriptive techniques. Based on the assessment through Instrumental Institutional design and governance, actual autonomy in exercising its mandate from the Westminster Foundation for Democracy (WFD), there are several low independence and accountability assessments, namely: (1) sufficiency of financial resources for performing its functions; (2) extent of autonomy to generate its own financial revenues; (3) security and stability of budget during past three years; and (4) stability of staff and extent of staff turn-over. In the future, ORI must improve several low scores of independence and accountability with its institutional relations to the DPR. Abstrak Ombudsman Republik Indonesia (ORI) merupakan lembaga yang berwenang mengawasi pelayanan publik yang dilakukan oleh penyelenggara negara, pemerintah, termasuk setiap orang dan badan hukum yang diberi tugas menyelenggarakan pelayanan publik tertentu yang pembiayaannya bersumber dari Anggaran Pendapatan dan Belanja Negara (APBN) dan Anggaran Pendapatan dan Belanja Daerah (APBD). Namun dalam menjalankan tugasnya, ORI berpotensi menghadapi tantangan independensi dan akuntabilitas dari Dewan Perwakilan Rakyat (DPR) yang menjalankan fungsi legislasi, penganggaran, dan pengawasan. Ketiga fungsi DPR tersebut terkait dengan keberadaan ORI dalam menjalankan tugasnya. Tulisan ini membahas tentang kedudukan, fungsi, dan hubungan kelembagaan antara ORI dan DPR. Metode yang digunakan adalah pendekatan kualitatif, dengan teknik pengumpulan data studi pustaka dan teknik analisis data melalui teknik deskriptif analitis kualitatif. Berdasarkan penilaian melalui Instrumental Institutional design and governance, otonomi aktual dalam menjalankan mandatnya dari Westminster Foundation for Democracy (WFD), terdapat beberapa penilaian independensi dan akuntabilitas yang rendah, yaitu: (1) kecukupan sumber daya keuangan untuk menjalankan fungsinya; (2) tingkat otonomi untuk menghasilkan pendapatan keuangannya sendiri; (3) keamanan dan stabilitas anggaran selama tiga tahun terakhir; dan (4) stabilitas staf dan tingkat pergantian staf. Ke depan, ORI harus memperbaiki beberapa skor independensi dan akuntabilitas yang rendah dengan hubungan kelembagaannya dengan DPR. Kata kunci: Ombudsman, DPR, Independensi, akuntabilitas